Clinical outcomes of endoscopic ultrasound-guided gastroenterostomy for gastric outlet obstruction: a systematic review and meta-analysis. Issue 2 (1st February 2022) - Fan, Wentao; Tan, Shali; Wang, Jiankun; Wang, Chengfan; Xu, Huan; Zhang, Lu; Liu, Li; Fan, Zhining; Tang, Xiaowei
Abstract: Background and aims: EUS-guided gastroenterostomy (EUS-GE) has been used for gastric outlet obstruction (GOO) with promising clinical outcomes. Therefore, we aimed to determine the clinical outcomes of EUS-GE for GOO. Material and methods: We used the keyword 'EUS-guided gastroenterostomy' to search in Pubmed, Web of science, Cochrane databases. Clinical outcomes of EUS-GE were evaluated in terms of technical success, clinical success and complications. Results: Ten studies reported 297 patients managed with EUS-GE. Weighted pooled rates (WPR) for technical success, clinical success and complications of EUS-GE were 91% (95%CI 87%-94%), 88% (95%CI 83%–91%) and 6.8% (95%CI 4.1%–11.0%). The most common complications were abdominal pain, 6.7% (95%CI 2.5%–16.5%) and bleeding, 4.8% (95%CI 1.5%–13.9%). Two studies compared EUS-GE with surgical gastrojejunostomy (SGJ). Pooled risk ratio (RR) for technical success, clinical success and complications were 0.87 (0.78, 0.97), I 2  = 0%; 0.92 (0.82, 1.04), I 2  = 0%; 0.28 (0.11, 0.68), I 2  = 0%. Three studies compared benign GOO with malignant GOO. RR for technical success and clinical success were 1.05 (0.82, 1.34), I 2  = 0%; 0.98 (0.72, 1.33), I 2  = 0%. Conclusions: Although EUS-GE and SGJ had similar clinical success rates, EUS-GE had a lower complication rate. EUS-GE is a safe, effective, and minimally invasive choice for patients with GOO.